The school of Salamanca and its quantitative theory of money - Carvalho, Suelem Halim Nardo de; Silva, Karla Maria da (Faculdade de Ciências e Letras - Unesp - Araraquara., 2022)
This research aimed to show that an existing intellectual tradition, the School of Salamanca, which, by being inserted in a historical context of consolidation of Modern Nation States and great commercial development worldwide, produced a significant number of works aimed at explaining commercial and financial activities. Contemporary to mercantilist economic politics, Salmantine authors, among other contributions, stood out for the development of the quantity theory of money, which, in practice, meant a monetary understanding antagonistic to bullionism.